2020
DOI: 10.3390/pr8101249
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Release Profile of Fibroblast Growth Factor-2-Load Mesoporous Calcium Silicate/Poly-ε-caprolactone 3D Scaffold for Regulate Bone Regeneration

Abstract: Recent advances in three-dimensional printing technology enable facile and on-demand fabrication of patient-specific bone scaffolds. However, there is still an urgent need for printable biomaterials with osteoinductivity. In the present study, we propose an approach to synthesize fibroblast growth factor-2 loaded-mesoporous calcium silicate nanoparticles. The growth factor loaded-nanoparticles served as fillers of polycaprolactone and then the composite scaffolds with a controlled pore structure were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…In order to overcome systemic side effects of medications and at the same time be able to stimulate bone regeneration, scientists have attempted to develop a stable drug-carrier system for the local release of osteoinduction and osteogenic factors [ 4 ]. To date, many reports regarding drug carrier systems have been published, and various types of material and scaffolds have been applied to investigate the effects of biocompatibility and osteogenic potential between bone tissue and bone defect site [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome systemic side effects of medications and at the same time be able to stimulate bone regeneration, scientists have attempted to develop a stable drug-carrier system for the local release of osteoinduction and osteogenic factors [ 4 ]. To date, many reports regarding drug carrier systems have been published, and various types of material and scaffolds have been applied to investigate the effects of biocompatibility and osteogenic potential between bone tissue and bone defect site [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A synergistic effect has also been observed for Si ions, which serve as efficient apatite nucleators. Ca ions serve as HA precipitation accelerators, thus causing HA precipitation [ 36 ]. Our XRD results demonstrate that the MS/CS scaffold has good in vitro bioactivity and biocompatibility.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated a decrease in the stiffness of the scaffolds after immersion that was similar to active biodegradation over time [ 39 , 40 ]. Previous research has discussed a correlation between the degradation and mechanical properties of 3D-plotted β-tricalcium phosphate scaffolds and cellular biological functions, including proliferation, adhesion, differentiation, and even in vitro regeneration [ 36 ]. The results are shown in Figure 4 and demonstrated that the MS/CS scaffold had good in vitro bioactivity, as seen with the initial increases in the mechanical properties during immersion.…”
Section: Resultsmentioning
confidence: 99%
“…CS products can be widely found on the market, and their biocompatibility and bioactivity have been widely discussed in the literature in the past decade [9,23,24]. CS had been shown to release Si ions, which have been proven to enhance vascularization by inducing the secretion of angiogenic-related factors from nearby fibroblasts [25]. Furthermore, the release of Si ions has also been found to promote hard tissue regeneration and to enhance odontogenic differentiation in various types of stem cells, notably hDPSCs [9].…”
Section: Introductionmentioning
confidence: 99%